Pelatihan Strategi Pengembangan SDM Dalam Persaingan Bisnis di Era Digital Pada PT. Perdana Persada Utama - Saragih, Nahar Maganda; Tanjung, Dahri Yani Hakim; Safira, Alisa (Publikasi Pengabdian Masyarakat, 2022)
Human resources can be described as the spearhead in the company's success, although in today's era of globalization makes some human resources in several sectors dysfunctional, in essence the existence of human resources remains a very important role in determining the progress of a company. The industrial revolution era of this generation has produced technological innovations that have a disruptive impact on business processes or people's lives. The existence of automation technology today makes the entire operational process of the company work automatically and can minimize errors and achieve work process efficiency. By definition, it appears that this technology involves minimal human intervention. The shift of the workforce which has now been taken up by automation technology has its own concerns about the employment aspect. Until there is speculation that the role of humans will be replaced by developing technology. This speculation is not impossible to be accepted by a company that is not able to create human resources that are not nimble and unable to compete in the digital era. In this service, the method used is to describe and explain and provide very detailed and detailed explanations and provide relevant examples to the company and conduct discussions and questions and answers, then direct training is held in their respective fields to see how systems that are already running and compare the systems that will run after the training. The result of this research on the community is that employees who follow abdimas understand both theoretically and practically related to self-development strategies to face the digital era in the days to come. After holding service to employees of PT. Perdana Persada Utama, employees can identify their competences and abilities more deeply and see opportunities for strategies that can improve performance and even self-actualization in their work so that employees are able to evaluate their own development and then apply the latest strategies for self-development as a resource. company human resources.